SISTEM PENGAJUAN PINJAMAN PADA BANK BRI UNIT CITAYAM DENGAN MENGGUNAKAN METODE WATERFALL - Sitorus, Michael; Yudha Utama, M. Astamar (Universitas Siber Indonesia, 2024)
Bank BRI Unit Citayam as a financial institution that collects funds from public in the form of deposits is channeled back to the community in the form of credit. The current implementation of applying for credit is less effective because when they come to the bank, and customer does not know the procedures and requirements for applying for credit. As a result, the customer must come back to the bank to complete the requirements. A web-based Loan Submission System (SPP) using the Waterfall method was created in order to provide convenience in the process of applying for a loan or credit. SPP was chosen because it has the advantage of easy access in carrying out the loan process and the data collection method used is simply observation, interviews and literature study. The purpose of this research is to design a SPP that can support the operational activities of loan applications.